Decreased IL-8 levels in CSF and serum of AD patients and negative correlation of MMSE and IL-1β - Hesse, Raphael; Wahler, Anke; Gummert, Pauline; Kirschmer, Stefanie; Otto, Markus; Tumani, Hayrettin; Lewerenz, Jan; Schnack, Cathrin; von Arnim, Christine A. F. (BMC neurology, 2016)
Background It is widely accepted that neuroinflammatory processes play an important role in the pathogenesis of Alzheimer’s disease (AD) and high levels of cytokines and chemokines are detected around Aβ plaques. Methods As neuroinflammation is involved in the development and progression of AD, we measured the pro-inflammatory cytokines interleukin 1β (IL-1β), IL-8 and tumor necrosis factor α (TNF-α) in serum and cerebrospinal fluid (CSF) samples from 45 AD patients and 53 age-matched control subjects using a highly sensitive multiplex electrochemiluminescence assay. To address the association with disease progression we correlated cognitive status with cytokine levels. Results CSF as well as serum IL-8 levels were found to be significantly lower in AD patients than in controls ( p = 0.02). A statistically significant inverse correlation was observed between the CSF level of IL-1β and the MMSE score (r s = -0.03, p = 0.02). We therefore stratified the AD patients by their MMSE scores into three equal groups and found that in the AD group with the most severe cognitive impairment CSF-IL-1β was significantly increased compared to age-matched controls ( p < 0.05), whereas in the other investigated groups the increase was not statistically significant. Conclusion Our results confirm data suggesting that cytokine alterations are involved in AD pathogenesis and may be helpful as a biomarker for monitoring disease progression.